Involvement of histamine H1 and H2 receptor inverse agonists in receptor's crossregulation - Díaz, Antonela Susana (2019)
Histamine [2-(4-Imidazolyl)-ethylamine] modulates different biological processes, through histamine H1 and H2 receptors, and their respective blockers are widely used in treating allergic and gastric acid-related disorders. Histamine H1 and H2 receptor crossdesensitization and cointernalization induced by its agonists have been previously described. In this study, we show how this crosstalk determines the response to histamine H1 and H2 receptor inverse agonists and how histamine H1 and H2 receptor inverse agonists interfere with the other receptor's response to agonists. By desensitization assays we demonstrate that histamine H1 and H2 receptor inverse agonists induce a crossregulation between both receptors. In this sense, the histamine H1 receptor inverse agonists desensitize the cAMP response to amthamine, a histamine H2 receptor agonist. In turn, histamine H2 receptor inverse agonists interfere with histamine H1 receptor signaling. We also determine that the crossdesensitization induced by histamine H1 or H2 receptor agonists alters the histamine inverse agonists receptor response: activation of histamine H1 receptor affects cAMP response induced by histamine H2 receptor inverse agonists, whereas histamine H2 receptor agonist induces a negative regulation on the anti-inflammatory response of histamine H1 receptor inverse agonists. Binding studies revealed that histamine H1 and H2 receptors cointernalize after stimulus with histamine receptor inverse agonists. In addition, the inhibition of the internalization process prevents receptor crossregulation. Our study provides new insights in the mechanisms of action of histamine H1 and H2 receptors that explain the effect of histamine H1 and H2 receptor inverse agonists and opens up new venues for novel therapeutic applications.